Characteristics And Mask Wearness Behavior Of Street Sweeper With Respiratory Complaints In Palembang City - Priyadi, Priyadi; Sunarsih, Elvi; Ambarsari, Ambarsari; Navianti, Diah (PT. Hafasy Dwi Nawasena, 2024)
Street sweepers are at high risk of exposure to air pollutants, making them vulnerable to respiratory problems. Therefore, preventive measures are necessary. This study used a descriptive observational survey with a cross-sectional design. The results indicated that 35 respondents (68.6%) had good knowledge about mask-wearing, 46 respondents (90.2%) had a positive attitude, and 36 respondents (70.6%) had sufficient actions regarding mask-wearing. Data analysis showed a p-value > 0.05, indicating no significant relationship between mask-wearing behavior and respiratory complaints. The conclusion is that while the behavior of wearing masks among street sweepers is not related to respiratory complaints, the length of service and education level are related to such complaints. These findings suggest that other factors, such as the duration of employment and education, play a more crucial role in influencing respiratory health among street sweepers. Thus, efforts to improve respiratory health should also focus on these aspects in addition to promoting mask usage.